(untitled) (Sirte University Journal of Humanities, 2022)
There is great importance for scientific families in the Islamic civilization. Andalusia has many families who has played a crucial role to enrich the scientific life during the different Islamic era there. One of these families is the family of Bano Zohr who’s several its members has specialized in medicine and gained wide fame and they became famous in the field of medicine through their achievements. The history of this family is full of personalities whose name was immortalized in the field of medicine, not only in Andalusia, but its resonance reached the far east, thus, they were able to leave a trail and legacy through the revolutions of their sons to the science of medicine over three centuries. That the family had raised doctors who left an imprint in the field of medicine. Their books were a reference for students of science and evidence of their skills in this industry. Through this study, we would like to shed light on the achievements of this family and get to know its most famous members, and how they could take the priority among the scientists of their era